2021
DOI: 10.1007/s10646-021-02495-2
|View full text |Cite
|
Sign up to set email alerts
|

In vitro cultivation of primary intestinal cells from Eisenia fetida as basis for ecotoxicological studies

Abstract: The earthworm Eisenia fetida is a commonly used model organism for unspecific soil feeders in ecotoxicological studies. Its intestinal cells are the first to encounter possible pollutants co-ingested by the earthworm, which makes them prime candidates for studies of toxic effects of environmental pollutants on the cellular as compared to the organismic level. In this context, the aim of this study was to demonstrate the suitability of preparations of primary intestinal E. fetida cells for in vitro ecotoxicolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…In addition, the coverage with an ecocorona 30 , that will certainly take place during digestion/composting, facilitates the internalization into cells 31 and therefore increases the risk associated with the ingestion of microplastic, e.g. by soil macrofauna 32 . Finally, the higher crystallinity and therefore higher resistance to further biodegradation extends the period of bioavailability of BDP microparticles with all the above-mentioned consequences.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the coverage with an ecocorona 30 , that will certainly take place during digestion/composting, facilitates the internalization into cells 31 and therefore increases the risk associated with the ingestion of microplastic, e.g. by soil macrofauna 32 . Finally, the higher crystallinity and therefore higher resistance to further biodegradation extends the period of bioavailability of BDP microparticles with all the above-mentioned consequences.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years the entry of plastic 1 , 2 and microplastic 1 , 3 12 materials into terrestrial ecosystems has increasingly become a concern. Especially microplastic contamination can have significant negative effects on terrestrial micro- and macrofauna 5 , 6 , 13 and has also been shown to impede plant biomass production 14 . For convenience, microplastic is often divided into large microplastic (1–5 mm) and small microplastic (< 1 mm).…”
Section: Introductionmentioning
confidence: 99%
“…The produced MP and submicron particles may have an even more adverse effects, since the number of particles and also their surface area available for interaction with the environment will increase as larger particles break down. The likelihood for uptake by cells and tissues also increases as particles get smaller, thereby increasing the possibility of negativec effects 13 , 19 , 20 .…”
Section: Introductionmentioning
confidence: 99%